2009
DOI: 10.1103/physrevd.80.124001
|View full text |Cite
|
Sign up to set email alerts
|

Teukolsky-Starobinsky identities: A novel derivation and generalizations

Abstract: We present a novel derivation of the Teukolsky-Starobinsky identities, based on properties of the confluent Heun functions. These functions define analytically all exact solutions to the Teukolsky master equation, as well as to the Regge-Wheeler and Zerilli ones. The class of solutions, subject to Teukolsky-Starobinsky type of identities is studied. Our generalization of the Teukolsky-Starobinsky identities is valid for the already studied linear perturbations to the Kerr and Schwarzschild metrics, as well as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 55 publications
0
37
0
1
Order By: Relevance
“…Next, we rederive the algebraically special perturbations of Kerr (the TTMs) as examples of finding polynomial solutions of the confluent Heun equation. The fact that some Heun polynomial solutions of the radial equation correspond to the TTMs is not new [29], but we feel it is important to include these examples for completeness. Finally, we make use of these Heun polynomial solutions for the TTMs in the limit that a = 0 to reexamine the existence of QNMs and TTM R s at special frequencies on the NIA.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we rederive the algebraically special perturbations of Kerr (the TTMs) as examples of finding polynomial solutions of the confluent Heun equation. The fact that some Heun polynomial solutions of the radial equation correspond to the TTMs is not new [29], but we feel it is important to include these examples for completeness. Finally, we make use of these Heun polynomial solutions for the TTMs in the limit that a = 0 to reexamine the existence of QNMs and TTM R s at special frequencies on the NIA.…”
Section: Introductionmentioning
confidence: 99%
“…The values of the parameters when the BH mass is M = 1/2 and, if we choose |r ∞ | = 20 which turns out to be large enough to simulate numerically the actual infinity, are ( [16,19]):…”
Section: General Form Of the Equationsmentioning
confidence: 99%
“…The indirect approaches like the continued fractions method have some limitations and are not directly related with the physics of the problem. The RWE, the Zerilli equation and TRE, however, can be solved analytically in terms of confluent Heun functions, as done for the first time in [16][17][18][19]. Imposing the boundary conditions on those solutions directly (see [13,17]) one obtains a system of spectral equations (1) and (2) featuring the confluent Heun functions which can be solved numerically.…”
mentioning
confidence: 99%
“…They showed that in those cases, the new method indeed works better than the standard methods. Therefore, the new method can be readily applied to find the roots of the Regge-Wheeler equation [18], the Zerilli equation [28], the Teukolsky radial and angular equations [24], all of which are solved analytically in terms of confluent Heun functions. Using this algorithm, we were able to solve directly the problem of quasi-normal modes of a Schwarzschild ( [9]) and Kerr black hole ( [10]) with higher precision than that of the Broyden method.…”
Section: Discussionmentioning
confidence: 99%